(untitled) (Baghdad Science Journal, 2004)
Thin films of ZnSe arc deposited on glass substrates by thermal evaporation in vacuum with different thickness (1000, 2700, 4000) A° temperature (293-373) °K are studies the electrical properties before and after annealing. The result show decrease D.0 conductivity and increasing the activation energy Eat.